WOMB CONTROL IN TONI MORRISON’S BELOVED - Yuniar Fatmasari (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study reveals the ideological strategies the dominant takes to exploit Black enslaved women’s womb experienced by the characters in Toni Morrison’s Beloved as well as their resistance. Written in 1987, the novel is set eight years after the end of the Civil War in time painful experiences during slavery era are still there in the mind of ex-enslaved Black women and men. The novel narrates the past through personal life experiences presented by Sethe and Baby Suggs. During slavery era, their bodies are not merely used to work in the plantation area but since they are women, their wombs are valuable commodity providing advantages and profit to the masters. To make it possible, the dominant function ideological strategies to control the Black enslaved women’s wombs. Therefore, this study tries to explore how the ideological strategies are practiced in the novel. According to Collins, creating negative images such as mammy, breeder woman, and jezebel addresses to the bodies of Black enslaved women belongs to ideological strategy which is more powerful compared to the economic and politic strategy. Each image covers dominant interest to control Black women’s womb under new-progressive capitalism in United States. The result of the study shows that those three images works effectively to control the Black enslaved women, even nowadays, those images are still there in the body of young generation of Black women and provide another form of womb’scontrol. However, the study as well finds out that the resistance toward the oppression is also varied. Self-definition is presumed to be a fundamental element to the journey of internalized oppression to the ‘free mind’ which eventually leads to the action of resistance. With this self-definition, Blackwomen begin to deny the existed negative images controlling their wombs.